Philosophy Between Technology and Probability: Niels Bohr and Carl Potter as Models – A Comparative Study (Al-Farooq Journal of Sciences, 2026)
The research aimed to uncover the epistemological foundations upon which Niels Bohr relied to undermine classical determinism through the "Principle of Complementarity," and to analyze Karl Popper’s critical vision that established "Falsifiability" as the criterion for the vitality of scientific truth. The research further sought to conduct a comparative study between ontological probability in quantum physics and methodological probability in critical rationalism, aiming to ground the contemporary concept of scientific objectivity as a procedural, probabilistic truth rather than an absolute essentialist one, and to deduce the dimensions of the human thought’s transition from the logic of necessity to the logic of possibility.The researcher used the critical-analytical method to deconstruct deterministic propositions and manifest the transition points from material certainty to the probability of tendencies, supported by the comparative method to facilitate intellectual confrontations between physical and logical perspectives. The study relied on qualitative analysis tools for the original texts of Bohr and Popper, employing logical deduction techniques to link physical findings with their profound philosophical implications.The research concluded that science has shifted from the dogmatism of certainty to a paradigm of probability—viewed as both a structural property of matter and a methodology for cognitive growth. This shift has redefined objectivity to become procedural, based on public scrutiny and flexibility in the face of cosmic complexity, while establishing scientific humility as an ethical necessity that ensures intellectual openness to a multiplicity of interpretations in a world characterized by becoming and uncertainty.The research recommended subjecting Artificial Intelligence outputs to the criterion of falsifiability to ensure the fluidity of critical review, and exporting the "Logic of Tendencies" to the social sciences to understand human phenomena as variable possibilities. It also called for integrating the philosophy of uncertainty into higher education programs and fostering a culture of continuous revision as a safeguard against intellectual closure in the digital age.